2007
DOI: 10.1042/bst0351610
|View full text |Cite
|
Sign up to set email alerts
|

Protein engineering applications of industrially exploitable enzymes: Geobacillus stearothermophilus LDH and Candida methylica FDH

Abstract: Enzymes have become important tools in several industries due to their ability to produce chirally pure and complex molecules with interesting biological properties. The NAD(+)-dependent LDH (lactate dehydrogenase) [bsLDH [Geobacillus stearothermophilus (formerly Bacillus stearothermophilus) LDH] from G. stearothermophilus and the NAD(+)-dependent FDH (formate dehydrogenase) [cmFDH (Candida methylica FDH)] enzyme from C. methylica are particularly crucial enzymes in the pharmaceutical industry and are related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Likewise, this result validates the designs and interpretations presented in our previous mutagenesis (Karaguler et al, 2007).…”
Section: Homology Modelling Of Cmfdhsupporting
confidence: 77%
“…Likewise, this result validates the designs and interpretations presented in our previous mutagenesis (Karaguler et al, 2007).…”
Section: Homology Modelling Of Cmfdhsupporting
confidence: 77%
“…For example, GOx and HRP catalyze redox transformations in sensing, catalysis, and waste-water remediation and they serve as cascade dyads. 1723 In contrast, LDH catalyzes dehydrogenation reactions for the production of enantiopure (−) lactate and 2-hydroxy acids that are precursors to many pharmaceutical drugs 24,25 and for sensing of lactate. 26 Hydrolases like AP are used widely for waste remediation, metal recovery, 27 and determination of surfactants, 28 whereas lipases are employed for the production of pharmaceutical drugs, cosmetics, leather, detergents, foods, perfumery, medical diagnostics and other synthetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that the N-terminal His tag does not influence the activity of cmFDH. 45,51 On the other hand, multi-histidine residues have a non-specific, yet considerable, high affinity to a variety of metal surfaces including gold. To avoid the unpredictable properties of poly-His affinity tag on newly introduced specific gold surface recognition ability, both the peptide-fused and control constructs were specifically designed by introducing a protease cleavage site at the end of poly-His tag region.…”
Section: Genetically Engineered Fdh With the Gold Surface Recognitionmentioning
confidence: 99%
“…[47][48][49] FDHs have been successfully isolated and produced from many different species, but methanol-consuming yeast species, such as Candida methylica (cm), have received the most attention due to the enhanced stability and relatively high activity of their isolated NAD + -dependent FDHs. 45,50,51 In this study, the authors genetically engineered NAD + -dependent FDH from C. methylica to couple with gold-binding peptide as a novel enzyme with chimeric properties. The resulting fusion enzyme was demonstrated to retain the catalytic activity both in solution-and surface-immobilised forms while gaining additional self-organisation ability verified on a variety of gold electrode surfaces.…”
Section: Direct Bioelectrocatalysis At the Interfaces By Genetically mentioning
confidence: 99%
See 1 more Smart Citation